HAK ATAS LINGKUNGAN HIDUP YANG BAIK DAN SEHAT BERDASARKAN UUD 1945 DALAM SISTEM HUKUM INDONESIA - Bella Ayu Anzalia; Dyna MT Pasaribu, Martua Felix Jonatan Simanullang, Natasya Adriani, Tessa Lonika Simanullang, Ramsu (Adisam Publisher, 2023)
The Constitution of the Republic of Indonesia of 1945 (UUDNRI) is a form of state constitution which is the result of an agreement of all Indonesian people to adapt to the development of the times and the rapid progress of environmental law because this research aims to analyze the constitutionality of the right to a living environment. good and healthy in the provisions of the article in relation to the protection of the environment, it can be recalled from the relationship between the two companies that the existence of norms or provisions regarding the environment or sustainable development concerns in the constitution will have a significant legal influence. Apart from that, environmentally friendly sustainable development requires policies for managing natural resources, controlling environmental risks and developing human economic policies. The environment is ultimately placed in a normative constitutional order to receive appropriate offers as part of elementary human rights. The movement to constitutionalize the right to a good and healthy environment is clear evidence of how important environmental issues are for today's modern generation to address. To enjoy a good and healthy environment and environmental protection from environmental pollution or environmental protection. In imposing obligations to maintain the environment and natural resources so that they can be enjoyed by future generations. This conference had an influence on the environmental awareness movement which was reflected in the development and increased attention to environmental issues and the formation of National Legislation. preserving the environment and natural resources so that they can be enjoyed by future generations. This conference had an influence on the environmental awareness movement which was reflected in the development and increased attention to environmental issues and the formation of National Legislation.